Entrepreneurship, neurodiversity & gender : exploring opportunities for enterprise and self-employment as pathways to fulfilling lives - Bennett, Dinah; Gibb, Yolanda K. (Emerald Publishing Limited, 2022)
Drawing on inspirational stories of neurodivergent entrepreneurs, Entrepreneurship, Neurodiversity & Gender provides insights into their respective journeys, challenges, and triumphs, alongside discussions with their allies and members of their ecosystem. Readers are offered innovations and solutions within the workplace and organisational design, employing both "neurodivergent" and "neurotypical" individuals to enable satisfying career paths for neurodivergent women. Entrepreneurship, Neurodiversity & Gender shines a spotlight on issues of intersectionality and opens the debate on how we can develop and support the options of entrepreneurship or self-employment that are offered to young people early on in their career. Yolanda Gill and Dinah Bennett aim to explore and foster greater awareness of and support through policy and practice. They also ask how can we ensure that the legal and policy environment does not create additional barriers to opportunities for enterprise and self-employment as pathways to fulfilling lives?